New indicator for the assessment of the life cycle of greenhouse gases emission of household refrigerating appliances - Khliyeva, Olga (Lviv Politechnic Publishing House, 2019)
refrigerating appliances based on the life cycle of GHG emission assessment is presented. A new eco-energy efficiency indicator is proposed. Calculation of the eco-energy efficiency indicator and traditional energy efficiency index for three household refrigerators has been performed. The qualitative difference in the results of comparison of these indicators for the analyzed refrigerators is shown.
Keywords: GHG emission; energy-saving; life cycle analysis; household refrigerating appliance